Fundamentals of Enhanced Oil Recovery - Kremieniewski, Marcin (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
For many years, the trend of increasing energy demand has been visible. Despite the search for alternative energy sources, it is estimated that oil and natural gas will be the main source of energy in transport for the next several dozen years. However, the reserves of renewable raw materials are limited in volume. Along with the degree of depletion, oil recovery becomes more and more difficult, even though the deposits are not yet completely empty. Therefore, it is essential to find new methods to increase oil and gas recovery. Actions aimed at intensifying oil recovery are very rational use of energy that has not yet been fully used. Usually, an increase in oil recovery can be achieved by using extraction intensification methods. However, measures to increase oil recovery can be implemented and carried out at any stage of the borehole implementation. Starting from the well design stage, through drilling and ending with the exploitation of oil and gas. Therefore, in order to further disseminate technologies and methods related to increasing oil recovery, a special edition has been developed, entitled "Fundamentals of Enhanced Oil Recovery". This Special Issue mainly covers original research and studies on the above-mentioned topics, including, but not limited to, improving the efficiency of oil recovery, improving the correct selection of drilling fluids, secondary methods of intensifying production and appropriate energy management in the oil industry.